2019
DOI: 10.1364/oe.27.020597
|View full text |Cite
|
Sign up to set email alerts
|

Inducing lasing in organic materials with low optical gain by three-dimensional plasmonic nanocavity arrays

Abstract: Lasing in organic media with very low gain has been pursued for a long time in optoelectronics. Here, we experimentally demonstrate that plasmonic lasing in the visible regime at room temperature can be achieved by hybridizing active media of very low optical gain such as ionic liquid and polymethylmethacrylate with three-dimensional (3D) plasmonic metamaterials. The 3D nanostructure consists of a double-layer N-shaped silver wire-hole array with strongly coupled multiple hot spots densely packed in each unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…For the operation wavelength around 1µm it was found that the gain level to required to achieve the superscattering condition is about 1760cm -1 . Such a gain level is attainable by using either organic dyes [37] or semiconductor materials [38].…”
Section: Single-layer Metasurfacementioning
confidence: 99%
“…For the operation wavelength around 1µm it was found that the gain level to required to achieve the superscattering condition is about 1760cm -1 . Such a gain level is attainable by using either organic dyes [37] or semiconductor materials [38].…”
Section: Single-layer Metasurfacementioning
confidence: 99%